2020
DOI: 10.1093/carcin/bgaa012
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants in m6A modification genes are associated with esophageal squamous-cell carcinoma in the Chinese population

Abstract: Abstract N 6-methyladenosine (m6A) is an abundant modification in RNAs that affects RNA metabolism, and it is reported to be closely related to cancer occurrence and metastasis. In this study, we focused on evaluating the associations between genetic variants in m6A modification genes and the risk of esophageal squamous-cell carcinoma (ESCC). By integrating data of our previous genome-wide association studies and the predictions of several annotation tools, we id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 46 publications
5
46
1
Order By: Relevance
“…Moreover, two clusters of ESCA presented signi cant difference in tumor stage, which also indicated that the expression pattern of these regulators were associated with the malignancy of ESCA. Previously, yang et al reported that genetic variants of m 6 A modi cation genes could affect the ESCA susceptibility [32]. In this study, we also found that genetic alteration of these gene was common in ESCA according to the cBio Cancer Genomics database.…”
Section: Discussionsupporting
confidence: 67%
“…Moreover, two clusters of ESCA presented signi cant difference in tumor stage, which also indicated that the expression pattern of these regulators were associated with the malignancy of ESCA. Previously, yang et al reported that genetic variants of m 6 A modi cation genes could affect the ESCA susceptibility [32]. In this study, we also found that genetic alteration of these gene was common in ESCA according to the cBio Cancer Genomics database.…”
Section: Discussionsupporting
confidence: 67%
“…Our functional experiments suggested that YTHDC2 could inhibit NSCLC proliferation and migration, which is different to the data reported by Tanabe et al 27 However, our results are consistent with the findings in ESCC. 16 Finally, the prognostic value of YTHDC2 in NSCLC was conducted via online database. Consistent with the conclusions in rectal cancer and head and neck squamous cell carcinoma, the Kaplan-Meier Plotter database validated that low expression of YTHDC2 indicates a poor prognosis in multiple types of cancer, including NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…reported that the YTHDC2 gene could be a potential candidate for pancreatic cancer susceptibility and a useful marker of early detection 15 . In addition, loss of YTHDC2 promoted the proliferation rate of esophageal squamous‐cell carcinoma (ESCC) by affecting several cancer‐related signaling pathways 16 . However, whether YTHDC2 is associated with NSCLC remains unknown and needs to be explored further.…”
Section: Introductionmentioning
confidence: 99%
“…SNPs can interfere with m 6 A methylation by altering the RNA sequences of target sites or key flanking nucleotides ( 118 ). Putative m 6 A-related SNPs (m 6 A-SNPs), which are close to or at the exact methylation site, can disrupt m 6 A modification and corresponding biological processes through multiple mechanisms, due to the location of m 6 A-SNPs, and can subsequently affect disease progression ( 119 ). m 6 A-SNPs have been recognized as a fundamental class of crucial multifunctional genetic variants associated with CVDs, which is concerning.…”
Section: M 6 a And Cardiovascular Diseasementioning
confidence: 99%